Pengaruh Motivasi dan Kemampuan Kerja terhadap Kepuasan Kerja dan Kinerja Karyawan Rumah Makan di Kota Wisata Yogyakarta, Indonesia - Annida Khoiriani (Asosiasi Ahli Administrasi Indonesia, 2021)
This study aims to analyze the effect of motivation and work ability on job satisfaction and the performance restaurant employees in Yogyakarta. Involving 100 respondents as research subjects. The research instrument in the form of a questionnaire, was developed based on instruments that have been used by other researchers and tested its validity and reliability before being distributed to the respondents of this study. The Statistical Package for The Social Sciences (SPSS) was used to test the hypothesis. The results of the analysis show that all the hypotheses of this study are proven. Where motivation and work ability have a significant effect on job satisfaction and performance of restaurant employees on average in Yogyakarta. The results of this study reinforce previous research and are consistent with several previous research themes. This is very useful for other researchers who will reexamine the research themes related to motivation, work ability, job satisfaction and employee performance.